DETERMINASI PERILAKU SEHAT: ANALISIS DESKRIPTIF PENGETAHUAN, SIKAP, DAN PERSEPSI RISIKO MASYARAKAT PEDESAAN TERHADAP DAMPAK KONSUMSI TEMBAKAU - Melva Melani; Saritha Siliawan (Jurnal Kesehatan Sejahtera, 2026)
Tobacco consumption remains a significant global epidemiological burden, particularly in rural areas with limited access to structured health information. Comprehensive knowledge and responsive attitudes are crucial foundations for reducing smoking prevalence at the community level. This study aims to analyze the level of knowledge, attitudes, smoking status, information sources, and community risk perceptions regarding the dangers of smoking in Nambiki Village, Langkat Regency. The quantitative research design used a descriptive cross-sectional approach. The study population included all residents aged ≥ 17 years and over in Nambiki Village. A sample of 100 respondents was selected using a simple random sampling technique. Data collection was conducted through structured interviews using a questionnaire that had been tested for validity and reliability. Data analysis used a descriptive univariate approach to generate frequency distributions and percentages. The majority of respondents had sufficient (45.0%) and insufficient (30.0%) knowledge. 58.0% of respondents expressed negative attitudes toward smoking control efforts. Active smoking status was recorded at 52.0%, with the majority of smokers smoking indoors. Social media (38.0%) and peers (25.0%) are the dominant sources of information compared to official health care channels (15.0%). Perception of the risk of degenerative diseases caused by smoking remains low, particularly in the perceived susceptibility dimension. Smoking behavior in rural areas is conditioned by low health literacy, permissive attitudes, and minimal penetration of health promotion by local medical authorities. Repositioning health promotion strategies based on local wisdom and optimizing digital channels is needed to change community risk perceptions.